HUBUNGAN TINGKAT EKONOMI ORANG TUA DENGAN PRESTASI BELAJAR SISWA KELAS V SD - Rahmawati Patta; Abd Kadir A; Nasruddin Nasruddin; Ainun Oktaviani (Universtas Negeri Makassar, 2022)
The problem in this study is that the economic level of different parents has a relationship with the learning achievement of fifth grade students in SD Gugus 4, Sibulue District, Bone Regency. Because parents who have a high economic level can meet the school needs of their children, as well as parents with lower economic levels do not pay attention to the school needs of their children because many basic needs must be met. The approach used in the research is a quantitative approach. The type of research used is descriptive research that is correlational. The data analysis technique used is Jaspen's correlation analysis technique. The results showed that the economic level of the parents of fifth grade elementary school students in Sibulue District, Bone Regency, was in the middle category or middle class, namely 57 students with a percentage of 85.07%. The learning achievement of fifth graders of SD Cluster 4, Sibulue District, Bone Regency is in the medium category, namely 45 students with a percentage of 67.16%. Then based on the results of inferential statistical analysis using the jaspen correlation of rcount (0.4182) rtable (0.2027) thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between the economic level of parents and the learning achievement of fifth grade elementary school students, Sibulue District, Bone Regency.